The Effect of Irisin as a Metabolic Regulator and Its Therapeutic Potential for Obesity - Hui Li; Fang Wang; Mu Yang; Jiao Sun; Yi Zhao; Dongqi Tang (International Journal of Endocrinology)
Obesity is a worldwide health problem due to the imbalance of energy intake and energy expenditure. Irisin, a newly identified exercise-responsive myokine, which is produced by the proteolytic cleavage of fibronectin type III domain-containing protein 5 (FNDC5), has emerged as a promising therapeutic strategy to combat obesity and obesity-related complications. Various studies in mice have shown that irisin could respond to systematic exercise training and promote white-to-brown fat transdifferentiation, but the role and function of irisin in humans are controversial. In this review, we systematically introduced and analyzed the factors that may contribute to these inconsistent results. Furthermore, we also described the potential anti-inflammatory properties of irisin under a variety of inflammatory conditions. Finally, the review discussed the existing unresolved issues and controversies about irisin, including the transcription of the irisin precursor FNDC5 gene in humans, the cleavage site of the yet unknown proteolytic enzyme that cleaves irisin from FNDC5, and the reliability of irisin levels measured with available detection methods.